PEMAHAMAN PRINSIP GERAKAN MUSLIM MODERN AL-RUJŪ‘ ILA AL-QUR’ĀN WA AL-SUNNAH - Rohmatul Maulidiana Aulia (Ushuluna: Jurnal Ilmu Ushuluddin, 2019)
The main problem discussed in this paper is Islamic Renewal by the Modern Muslim  movement.  This  movement  is  a  response  to  the  reality  of  Muslims  who contradict the understanding of ijtihad Modern Muslims. Under the pretext of enforcing the authority of the Qur'an and sunna consequently so that Muslims can practice and re-live the pure teachings of Islam and revive the spirit of ijtihad and leave the habit of taklid. This paper discusses the understanding of al-Rujū 'ila al-Qur'an wa al-Sunnah, especially by modernists. This paper will describe analytically and critically explore the modernist view of the principle of al-Rujū 'ila al-Qur'an wa al-Sunnah.